Do You Really Want to Share Everything? The Wellbeing of Work-Linked Couples - Juliane Hennecke; Clemens Hetschko (Institute of Labor Economics (IZA), 2021)
Work as well as family life are crucial sources of human wellbeing, which however often interfere. This is especially so if partners work in the same occupation or industry. At the same time, being work-linked may benefit their career success. Still, surprisingly little is known about the wellbeing of work-linked couples. Our study fills this gap by examining the satisfaction differences between work-linked and non-work-linked partners. Using data from the German Socio-Economic Panel (SOEP, 2019), we estimate the effect of working in the same occupation and/or industry on life satisfaction as well as satisfaction with four areas of life: income, work, family and leisure. In the process, we employ pooled OLS estimations and instrumental variable strategies, for instance based on the gender disparity in industries and occupations. Our results suggest that being work-linked increases satisfaction with life as well as income and job satisfaction. These findings are consistent with positive assortative matching and mutual career support between work-linked partners. Our conclusions concern hiring couples as a means of recruiting exceptional talent.
Keywords: I31; J12; J21; J44; M51; 330; occupational gender disparity; copreneurs; work-life balance; relationship quality; assortative matching; wellbeing; work-linked couples; dual career support